2007
DOI: 10.1530/rep-06-0201
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa stimulate prostaglandin synthesis and secretion in bovine oviductal epithelial cells

Abstract: The dynamic action of oviductal secretory compounds on spermatozoa function is well documented. In contrast, the effect of spermatozoa on oviductal function remains poorly characterized. Previously, our lab and others have shown that prostaglandin (PG), together with other vasoactive peptides, plays major roles in oviductal contractions and sperm transport. We therefore examined the effect of spermatozoa on the production of PG by cow oviductal epithelial cells (OEC). A bovine spermatozoa-OEC co-culture system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 33 publications
(37 reference statements)
3
55
0
Order By: Relevance
“…In an in vivo study in mice, the expression of ADM and prostaglandin was reported to be upregulated after the arrival of sperm in the oviduct (Fazeli et al 2004). A similar report showed that motile spermatozoa increased the secretion of prostaglandin and vasoactive peptides from the bovine oviduct in culture (Kodithuwakku et al 2002). These findings suggest that sperm may increase CBF via the release of ADM and other substances -a suggestion that is upheld by our results in this study.…”
Section: Discussionsupporting
confidence: 75%
“…In an in vivo study in mice, the expression of ADM and prostaglandin was reported to be upregulated after the arrival of sperm in the oviduct (Fazeli et al 2004). A similar report showed that motile spermatozoa increased the secretion of prostaglandin and vasoactive peptides from the bovine oviduct in culture (Kodithuwakku et al 2002). These findings suggest that sperm may increase CBF via the release of ADM and other substances -a suggestion that is upheld by our results in this study.…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, SEM analysis demonstrated that PGE 2 significantly reduced the formation of NETs and suppressed the phagocytosis of sperm by PMNs, as observed in PMNs treated with the LH-stimulated BOEC supernatant. Moreover, sperm stimulate the secretion of PGE 2 by cultured BOECs (Kodithuwakku et al 2007). Thus, in addition to the action of LH, sperm may have a self-protective mechanism by the suppression of the phagocytic activity of PMNs through further enhancement of PGE 2 secretion in the microenvironment surrounding them.…”
Section: Sperm Phagocytosis By Pmns In Bovine Oviductmentioning
confidence: 99%
“…These culture systems have been used to obtain valuable information on gene and protein expression (Umezu et al 2003). They have also been used to gain a better understanding of the maternal interaction with gametes and embryos (Lee et al 2002;Fazeli et al 2004;Georgiou et al 2007;Kodithuwakku et al 2007;Ulbrich et al 2010). …”
Section: Introductionmentioning
confidence: 99%